(untitled) (Research, Society and Development, 2022)
This theoretical article aims to analyze the results of national productions on the state of knowledge in academic research on Mathematical Modeling in High School. The methodological procedures were through bibliographic research, through a systematic review of the literature, a method that provides the search for the necessary knowledge about the theme in the area of ​​Teaching and Mathematical Education. The articles were collected from the following databases: SciELO and CAPES Journal Portal, the search was carried out in the months of November and December 2020. Based on the results of the studies of this review, it was possible to realize that the focus of the research is centered on the reflections and reports of experiences of teachers and students about modeling activities in high school classrooms. He also pointed out that the authors of the analyzed studies highlight, as a positive aspect, the contribution of other areas of knowledge in the applicability of mathematical knowledge and in solving problem situations related to students’ daily lives. From the analysis, we conclude that Mathematical Modeling is a consolidated practice in Mathematics Education, and contributes significantly to the development of students’ learning during the educational process.